2019
DOI: 10.1177/0046958019865831
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study Evaluating and Comparing the Health Literacy Knowledge and Communication Skills Used by Nurses and Physicians

Abstract: Health literacy (HL) is considered as an interaction between the demands of health systems and the skills of individuals. The current global approach demands health professionals to be more accountable for universal precautions approach and improve communication skills, and employ strategies to confirm patients’ understanding. The aim of this study is to assess the knowledge and attitude of health care professionals (HCPs) about HL and their communication skills, and its effect on their practices, and to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
4
20
0
3
Order By: Relevance
“…This is similar in other country contexts. Research by Guner and Ekmekci (2019) showed that healthcare professionals in Turkey had limited awareness and knowledge on health literacy and its impact on their patients [16], and significant differences existed between nurses and physicians: awareness was higher among nurses than among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar in other country contexts. Research by Guner and Ekmekci (2019) showed that healthcare professionals in Turkey had limited awareness and knowledge on health literacy and its impact on their patients [16], and significant differences existed between nurses and physicians: awareness was higher among nurses than among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy refers to skills such as reading, writing, numeracy, communication, and the use of electronic technology ( Güner & Ekmekci, 2019 ) that are necessary to make appropriate health decisions and navigate the healthcare system. To ensure representation of major user groups as required by FDA, it is recommended that patients are stratified based on expected health literacy, often assessed via an Agency for Healthcare Research and Quality (AHRQ) health literacy survey tool ( Agency for Healthcare Research and Quality, 2020 ), such as the Short Assessment of Health Literacy ( Lee et al, 2010 ) or Rapid Assessment of Adult Literacy in Medicine ( Arozullah et al, 2007 ).…”
Section: Recruitment Considerations For Patient-facing Devicesmentioning
confidence: 99%
“…Other recommendations are to avoid medical jargon, use smaller and more manageable concrete steps to break down instructions, and assess comprehension ( Hersh et al, 2015 ). Instructional videos, in comparison to textual information, have also been shown to be effective communication tools to increase memory retention and patient satisfaction ( Güner & Ekmekci, 2019 ; Sharma et al, 2018 ). As important as these recommendations are for in-person studies, they will be even more critical for remote studies.…”
Section: Recruitment Considerations For Patient-facing Devicesmentioning
confidence: 99%
“…Trust can be established by nurses through empathic communication, communication immediacy, warmth, and most important, the practice of self-reflection and reflexivity to minimize personal, implicit biases (Wesp et al, 2018). These interpersonal communication skills and intentional reflection among nurses should be emphasized in nursing education in the preparation of professional nurses (Güner & Ekmekci, 2019) as well as in health care institutions in the form of continuing education for health care professionals.…”
Section: Recommendations For Nurses and Health Care Professionals In mentioning
confidence: 99%